(untitled) (Cadernos de Ética e Filosofia Política, 2019)
This paper of Victor Brochard was originally published in the Revue Philosophique, in 1901. It examines the differences between the ancient moral and the modern moral, particularly the absence in the ancient moral of the notion of ought and the obligation, elucidating the motives by which the moderns adopt these notions